Selecting feasible standard form of construction contracts using text analysis. (April 2022) - Elkhayat, Yasmine; Marzouk, Mohamed
Highlights: Selecting the most appropriate Standard Form of Construction Contract (SFCC) Applying text analysis and hybrid multi criteria decision-making techniques in SFCC Selection. Identifying five main aspects in selecting the appropriate SFCC. Extracting hidden information found in unstructured data in clauses and provisions of three SFCCs. Advising the user for some tips to be considered in the contract formation stage. Abstract: Delivering successful projects requires establishing a well-drafted contract, through setting balanced rights and obligations. Nowadays, Standard Forms of Construction Contracts (SFCCs) are being utilized, aiming to manifest the contractual relationships between the parties. This research aims to develop a model that helps in selecting the most appropriate SFCC using text analysis and multi-criteria decision-making techniques. This research studies three SFCCs which are: 1 (FIDIC Red Book 2017, 2 (JCT Standard Building Contract with Quantities 2016, and 3) NEC4 Engineering and Construction Contract. The research compares SFCCs in terms of five aspects which are: 1) Readability, 2) Sharing common goals, 3) Loss and rewards, 4) Dealing with uncertainties, and 5) Suspension by parties. Literature emphasized that these aspects were proven to be crucial in achieving a successful contract agreement. The research starts with contract analysis to extract insights for the selected SFCCs. Where the clauses and provisions of the three SFCCs are compared based on the output of the text analysis process. Accordingly, questions are developed to assist the user in selecting the most suitable SFCC based on a hybrid Multi-Criteria Decision-Making model. Finally, a recommendation system is developed to advise the user for critical success factors to be considered in the contract formation stage. This study adds to the body of knowledge of contract management and aids in proactively avoiding or mitigating conflicts and disputes, by reducing the contractual-related problems that may take place due to inappropriate contract types or provisions.